A gain‐of‐function mutation in TNFRSF13B is a candidate for predisposition to familial or sporadic immune thrombocytopenia. (13th September 2017) - Peng, H.‐L.; Zhang, Y.; Sun, N.‐N.; Yin, Y.‐F.; Wang, Y.‐W.; Cheng, Z.; Yan, W.‐Z.; Liu, S.‐F.; Xu, Y.‐X.; Xiao, X.; Zhang, G.‐S.
Abstract : Essentials Positive family histories suggest the existence of hereditary immune thrombocytopenia (ITP). The predisposing gene for familial ITP was screened in two familial ITP patients. The G76S mutation on TNFRSF13B led to immune dysfunction and induced megakaryocyte apoptosis. The G76S mutation on TNFRSF13B is a gain‐of‐function mutation and a predisposing variant for ITP. Summary: Background: Most immune thrombocytopenia (ITP) is sporadic but a positive family history of ITP in some patients suggests that hereditary forms exist. Because of the rarity of familial ITP families available for study and the heterogeneity of sporadic ITP, family linkage analysis or genome‐wide association studies are limited. Objectives: Based on one ITP pedigree, we try to identify the predisposing gene in familial or sporadic ITP and reveal the way in which it causes thrombocytopenia. Methods: Gene expression profiling analysis and whole‐exome sequencing were performed on samples from family members with ITP, sporadic ITP cases and healthy individuals. We also evaluated the influence of potential pathogenic mutation on immune function and megakaryocyte apoptosis. Results: Whole‐exome sequencing identified a potential pathologic p.G76S heterozygous mutation on the TNFRSF13B gene in familial ITP patients. ITP patients harboring the G76S mutation displayed an upregulated 'cytokine–cytokine receptor interaction' signal, increased serum TNFα, IL‐17α, IFNγ and BAFF levels, and enhanced binding capacity of APRIL ligand to B cells. Additionally, Epstein‐Barr virus (EBV)‐transformed B cells with the G76S mutation could induce human megakaryocyte line (Meg‐01) apoptosis significantly. Conclusion: p.G76S mutation on the TNFRSF13B gene is responsible for ITP, and is a genetic predisposing factor for familial or sporadic ITP.